THE EFFECT OF PATIENT EXPERIENCE AND PRICE FAIRNESS ON MEDIATED REVISIT INTENTION BY OUTPATIENT PATIENT SATISFACTION AT ABDUL RADJAK HOSPITAL, SALEMBA - Julianty Arisandi Nasution; Saparso; Wani Devita Gunardi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The purpose of this study is to analyze the influencepatient experience and price fairness on revisit intention with patient satisfaction as a mediating variable. The research method used is quantitative with a survey approach. Data were collected through questionnaires filled out by outpatients at Abdul Radjak Salemba Hospital. The measurement scale used in the questionnaire was the Likert Scale. The research sample consisted of 170 patients and was selected using a purposive sampling technique. The data analysis technique used Partial Least Square-Structural Equation Modeling (PLS-SEM). Based on the results of the direct effect hypothesis test, it shows that patient experience and price fairness have a positive and significant effect on revisit intention, patient experience and price fairness have a positive and significant effect on patient satisfaction, patient satisfaction has a positive and significant effect on revisit intention. The results of the indirect effect hypothesis test show that patient experience and price fairness have a positive and significant effect on revisit intention through patient satisfaction. Suggestions for the management of Abdul Radjak Salemba Hospital in an effort to increase revisit intention in outpatients by paying attention to patient experience factors, price fairness, and satisfaction.